2015
DOI: 10.1002/stc.1767
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement method of support vector machine-based model monitoring dam safety

Abstract: Summary Under the comprehensive influence of material and loads, dam structural behavior presents the time‐varying nonlinear characteristics. To forecast the dam structural behavior (displacement, stress, seepage, etc.), the models monitoring dam safety are often built according to the prototype observations on dam safety. However, the modeling process is usually fulfilled with the offline and static pattern. As time goes on, the fitting and forecasting ability of built static model will decline gradually. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 26 publications
(41 reference statements)
0
69
0
Order By: Relevance
“…Recently, SVM has been utilized to model complex civil engineering problems to provide an extensive understanding of the variables involved in the model [9][10][11][12][13][14][15][16].In the majority of the conducted researches, SVM is utilized to predict specific responses depending on the input variables or to simulate performance of a particular engineering system with special conditions. For example, in hydraulic structure design, SVM has been used to predict the forecasting of the tangential shift of a concrete dam [14], and to predict future dam responses with environmental variables [17].…”
Section: Construction Of Hydraulic Water Retainingmentioning
confidence: 99%
“…Recently, SVM has been utilized to model complex civil engineering problems to provide an extensive understanding of the variables involved in the model [9][10][11][12][13][14][15][16].In the majority of the conducted researches, SVM is utilized to predict specific responses depending on the input variables or to simulate performance of a particular engineering system with special conditions. For example, in hydraulic structure design, SVM has been used to predict the forecasting of the tangential shift of a concrete dam [14], and to predict future dam responses with environmental variables [17].…”
Section: Construction Of Hydraulic Water Retainingmentioning
confidence: 99%
“…First, the data series of single monitoring point is taken to analyze its characteristic values and build its mathematical model with Kalman filter method, support vector machine method, and artificial neural network method. Then the information fusion for monitoring points with the same type is implemented to construct the space–time model describing quantitatively dam structural behavior …”
Section: Multisource Information Fusion‐based Diagnosing Framework Ofmentioning
confidence: 99%
“…Thus, k v can be approximately regarded as the permeability coefficient of the RCC dam when the layer does not exist. According to the literature, the relationship curve between the measuring head and the reservoir water level at the measuring point under different reservoir water levels is obtained by the finite element analysis method of seepage. The following polynomial is obtained by a further fitting solution: φ1()H=i=0q1aiHi, where a i is the fitting coefficient of water pressure, q 1 is the number of factors, and H is the upstream water depth.…”
Section: Mathematical Model Of Spatial Seepage For Rcc Dammentioning
confidence: 99%
“…We carried out a basic research on the mechanical characteristics of RCC dams and found that their interlayer seepage characteristics are different from that of the RCC noumenon, and the effect zone is an important factor in the percolation state analysis of RCC dams. The permeability of RCC dams is influenced by factors, such as reservoir level, rainfall, temperature, and aging . According to the seepage monitoring data analysis, the influence of the reservoir water level and rainfall on the seepage of dams has a lag effect .…”
Section: Introductionmentioning
confidence: 99%